2022
DOI: 10.1371/journal.pone.0263922
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting existing deterioration indices with chest radiographs to predict clinical deterioration

Abstract: Importance When hospitals are at capacity, accurate deterioration indices could help identify low-risk patients as potential candidates for home care programs and alleviate hospital strain. To date, many existing deterioration indices are based entirely on structured data from the electronic health record (EHR) and ignore potentially useful information from other sources. Objective To improve the accuracy of existing deterioration indices by incorporating unstructured imaging data from chest radiographs. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Using ICD codes to identify patients may lead to some misclassification; however, we required multiple visits within a specific time to reduce potential false positives. The complexity challenges of using ICD codes and other structured data for identifying cases are myriad, and one way to overcome these biases is to include unstructured data (or clinic notes) in developing computational phenotyping algorithms ( 22 , 23 ). We found that the prevalence of individual COPCs in our study is lower than other recently published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using ICD codes to identify patients may lead to some misclassification; however, we required multiple visits within a specific time to reduce potential false positives. The complexity challenges of using ICD codes and other structured data for identifying cases are myriad, and one way to overcome these biases is to include unstructured data (or clinic notes) in developing computational phenotyping algorithms ( 22 , 23 ). We found that the prevalence of individual COPCs in our study is lower than other recently published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Epic’s Deterioration Index (DI) is one of the most widely used early warning systems deployed in hundreds of hospitals across the United States [1] , [2] . This system aims to detect patients who deteriorate and require higher levels of care.…”
Section: Introductionmentioning
confidence: 99%
“…The high-risk patients are at the greatest risk of encountering a composite adverse outcome which can be prevented by prompt interventions. This has been found to have fair performance and improve patient outcomes and reduce ICU admissions [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epic’s Deterioration Index (EDI) is a proprietary algorithm and one of the most widely used EWS deployed in hundreds of hospitals across the US. 3 , 4 This system generates a patient risk score after hospital admission, and it is then regularly calculated based on most recent available data at 15-min intervals until discharge. A DI score value ranges between 0 and 100, defining low (<30 green), intermediate (30–60 orange), or high risk (>60 red) of a composite AE: all-cause mortality, cardiac arrest, transfer to intensive care, and evaluation by the rapid response team.…”
Section: Introductionmentioning
confidence: 99%